Building a Decision Support System based on Data-Driven Approach to Enhancing Teaching Quality - Trịnh Thị Mỹ Hiền; Lê Thị Phương; Nguyễn Hoàng Hy; Bùi Thị Hương Giang; Huỳnh Tuấn Anh; Nguyễn Đình Hiển (Journal of Technical Education Science, 2024)
In the current era of Industry 4.0, the analysis and evaluation of data, leading to informed decision-making, play a crucial role in advancing all aspects of life. At University of Information Technology (VNU-HCM), students have the opportunity to assess and provide feedback on teching activities of lecturers at the end of each semester, resulting in an increasingly large dataset. Consequently, the potential of this dataset is immense. To help the university efficiently capture valuable information and support decision-making aimed at improving teaching quality, this study develops a decision support system, named Academic Quality Assurance, for supporting the analyzing of data collected from multiple semesters. The system focuses on assisting users in filtering data based on semesters, courses, departments, and programs, and then visualizing the data, providing comparisons. In turn, this supports users in making necessary improvement decisions and tracking effectiveness through annual evaluation scores. In the following, the system will be elaborated further on the process of constructing survey questions, building the dataset, survey data structure.